2014
DOI: 10.1007/s40069-014-0087-y
|View full text |Cite
|
Sign up to set email alerts
|

Mix Design and Properties of Recycled Aggregate Concretes: Applicability of Eurocode 2

Abstract: This work is devoted to the study of fresh and hardened properties of concrete containing recycled gravel. Four formulations were studied, the concrete of reference and three concretes containing recycled gravel with 30, 65 and 100 % replacement ratios. All materials were formulated on the basis of S4 class of flowability and a target C35 class of compressive strength according to the standard EN 206-1. The paper first presents the mix design method which was based on the optimization of cementitious paste and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 33 publications
2
44
0
3
Order By: Relevance
“…Compared with natural coarse aggregates (NCA), recycled coarse aggregates (RCA) have substantial characteristics in terms of uncertainties that arise from their complex composition (Wardeh et al 2015). It is well-known that the properties of recycled aggregate concrete (RAC) are different from those of natural aggregate concrete (NAC) (Yehia et al 2015;Wardeh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with natural coarse aggregates (NCA), recycled coarse aggregates (RCA) have substantial characteristics in terms of uncertainties that arise from their complex composition (Wardeh et al 2015). It is well-known that the properties of recycled aggregate concrete (RAC) are different from those of natural aggregate concrete (NAC) (Yehia et al 2015;Wardeh et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with natural coarse aggregates (NCA), recycled coarse aggregates (RCA) have substantial characteristics in terms of uncertainties that arise from their complex composition (Wardeh et al 2015). It is well-known that the properties of recycled aggregate concrete (RAC) are different from those of natural aggregate concrete (NAC) (Yehia et al 2015;Wardeh et al 2015). Previous theoretical analyses carried out in the framework of structural reliability theory and lab experiments have shown that: (1) higher scatter of the compressive strength of RAC affects the margins of structural safety (Breccolotti and Materazzi 2010); (2) the compressive strength of RAC varies with the RCA replacement percentage and it follows a normal probability distribution (Li et al 2006); and (3) the durability of RAC can be strongly affected by the porosity and the high water absorption of the RCA (Debieb et al 2010;Kou and Poon 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It was pointed out in 17 studies (Fathifazl 2008) that the elastic modulus of RCA concrete decreased by 0-45%, compared to that of the companion natural aggregate concrete. Other researchers also confirmed that RCA concretes had lower elastic modulus than normal aggregate one (Tavakoli and Soroushian 1996;Eguchi et al 2007;Padmini et al 2009;Limbachiya et al 2012;McNeil and Kang 2013;Wardeh et al 2015). This means that the elastic modulus of RCA concrete is a function of that of the mortar and also has a proportional relationship with the volume of the mortar (Fathifazl 2008).…”
Section: Introductionmentioning
confidence: 79%
“…Se pudo observar que la densidad de los agregados reciclados es menor en relación con los naturales; esta leve disminución se debe también a aquella fracción de mortero que queda adherido y cuya porosidad es mayor a la piedra natural lo cual genera que la densidad se vea levemente afectada (Safiuddin, 2011, McNail, K y Kang, 2013Wardeh et al, 2014).…”
Section: Figura 7 Morfología De Las Partículas De Agregados Gruesosunclassified